Mechanisms underlying CSD initiation implicated by genetic mouse models of migraine - Daniela Pietrobon; K.C. Brennan (The Journal of Headache and Pain)
Abstract A key unanswered question in migraine neurobiology concerns the mechanisms that make the brain of migraineurs susceptible to cortical spreading depression (CSD, a spreading depolarization that underlies migraine aura and may trigger the migraine pain mechanisms). Important insights into this question can be obtained by studying the mechanisms of facilitation of CSD initiation in genetic mouse models of the disease. These models, all generated from families with hereditary migraine, allow the investigation of the functional consequences of disease-causing mutations at the molecular, cellular, synaptic and neural circuit levels. In this review, after describing the available genetic mouse models of migraine, which all share increased susceptibility to experimentally induced CSD, we will discuss the functional alterations in their cerebral cortex and the mechanisms underlying the facilitation of CSD initiation in their cortex, as well as the insights that these mechanisms may give into the mechanisms of initiation of spontaneous CSDs in migraine.